Meta-Analysis: Effect of Oral Contraceptives on Breast Cancer - Siti Nur Hanifah; Bhisma Murti; Eti Poncorini Pamungkasari (Masters Program in Public Health, 2022)
Background: Breast cancer is a disease characterized by abnormal cell growth in the breast. Until now, breast cancer is a life-threatening disease in women and is the main cause of death among the female population. Oral contraceptives or pills are one of the risk factors for women developing breast cancer. This study aims to determine the effect of oral contraceptives on the incidence of breast cancer.Subjects and Method: This research is a meta-analytical study and a systematic review. The articles used were obtained from several electronic databases including PubMed, Google Scholar and ScienceDirect. The keywords to search for articles were as follows: Determinant OR risk factor AND breast cancer AND hormonal contraceptive OR oral contraceptive AND case control study. The article under study is a full text article with an observational study design. Articles were collected using the PRISMA diagram, and analyzed using the Review Manager 5.3 application.Results: A total of 9 case control studies involving 6,811 women with breast cancer from several countries in Asia, Africa, and North America were selected for meta-analysis and systematic review. The data collected showed that women who used oral contraceptives had a risk of developing breast cancer as much as 1.82 times than those who did not use oral contraceptives (aOR= 1.82; 95% CI= 1.43 to 2.33; p<0.001).Conclusion: Use of oral contraceptives increases the risk of developing breast cancer. Keywords: oral contraceptives, breast cancer. Correspondence:Siti Nur Hanifah. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: sitinurhanifah21@yahoo.com. Mobile: 085204219736.